2016
DOI: 10.1101/gad.274951.115
|View full text |Cite
|
Sign up to set email alerts
|

αE-catenin inhibits a Src–YAP1 oncogenic module that couples tyrosine kinases and the effector of Hippo signaling pathway

Abstract: Cell-cell adhesion protein αE-catenin inhibits skin squamous cell carcinoma (SCC) development; however, the mechanisms responsible for this function are not completely understood. We report here that αE-catenin inhibits β4 integrin-mediated activation of SRC tyrosine kinase. SRC is the first discovered oncogene, but the protein substrate critical for SRC-mediated transformation has not been identified. We found that YAP1, the pivotal effector of the Hippo signaling pathway, is a direct SRC phosphorylation targ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
195
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(205 citation statements)
references
References 58 publications
10
195
0
Order By: Relevance
“…Our findings re-enforce the important oncogenic function of YAP (21) and explain the basis for its frequent activation in CRC and possibly other epithelial tumors that are devoid of mutations that disrupt Hippo signaling. Indeed, the SFK-YAP module also functions in skin cancer (33). YAP up-regulation in epithelial cancers is also known to account for acquired drug resistance (21), but the underlying mechanisms were not reported.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings re-enforce the important oncogenic function of YAP (21) and explain the basis for its frequent activation in CRC and possibly other epithelial tumors that are devoid of mutations that disrupt Hippo signaling. Indeed, the SFK-YAP module also functions in skin cancer (33). YAP up-regulation in epithelial cancers is also known to account for acquired drug resistance (21), but the underlying mechanisms were not reported.…”
Section: Discussionmentioning
confidence: 99%
“…One possible mechanism for this observation could be physical interactions between α-catenin and Merlin [66], which could localize Merlin to adherens junctions, although Merlin also associates with tight junction proteins [67]. It was also recently reported that α-catenin inhibits a direct activation of YAP by Src [68]. Whether mammalian homologues of Ds and Fat (Dchs1 and Fat4) regulate the Hippo pathway in mammalian cells is also controversial, as there have been conflicting reports about whether they influence Yap activity [69-71].…”
Section: Dynamic Localization Of Hippo Pathway Componentsmentioning
confidence: 99%
“…As activation of FAK by integrins can be modulated by substrate stiffness [97], regulation of Hippo signaling through FAK could also contribute to influences of the mechanical environment on Hippo signaling, . An alternative mechanism by which Src can promote YAP activity, involving direct phosphorylation of tyrosines residues on YAP by Src, has also recently been described [68, 98]. …”
Section: Regulation Of Hippo Signaling By the Extracellular Matrixmentioning
confidence: 99%
“…On the other hand, p120 directly stabilizes and retains E-cadherin at the cell surface by suppressing E-cadherin endocytosis (19,(24)(25)(26) and coordinates local interactions with the cytoskeleton through recruitment of various RhoGTPase modulators (e.g., RhoGEFs, RhoGAPs, Rho kinase 1 [ROCK1], FRMD5) (27)(28)(29)(30). Other important signaling systems that interface physically and/or functionally with the E-cadherin complex include the Wnt pathway (e.g., APC, β-catenin) (31), the HIPPO pathway (including downstream effectors YAP and TAZ) (32,33), receptor tyrosine kinase (RTK) pathways (e.g., EGFR and downstream effectors) (34)(35)(36), the TGFβRII pathway (37), and NF-κB signaling (38,39). Most of these pathways have oncogenic potential when dysregulated and function in opposition to the growth-suppressive effects of the E-cadherin complex in differentiated epithelia.…”
Section: P120 Functions As An Obligatory Haploinsufficient Tumor Suppmentioning
confidence: 99%